Reduced graphene oxide anodes for potential application in algae biophotovoltaic platforms - Ng, Fong Lee; Jaafar, Muhammad Musoddiq; Phang, Siew Moi; Chan, Zhijian; Salleh, Nurul Anati; Azmi, Siti Zulfikriyah; Yunus, Kamran; Fisher, Adrian C.; Periasamy, Vengadesh (Nature Publishing Group, 2014)
The search for renewable energy sources has become challenging in the current era, as conventional fuel sources are of finite origins. Recent research interest has focused on various biophotovoltaic (BPV) platforms utilizing algae, which are then used to harvest solar energy and generate electrical power. The majority of BPV platforms incorporate indium tin oxide (ITO) anodes for the purpose of charge transfer due to its inherent optical and electrical properties. However, other materials such as reduced graphene oxide (RGO) could provide higher efficiency due to their intrinsic electrical properties and biological compatibility. In this work, the performance of algae biofilms grown on RGO and ITO anodes were measured and discussed. Results indicate improved peak power of 0.1481 mWm(-2) using the RGO electrode and an increase in efficiency of 119%, illustrating the potential of RGO as an anode material for applications in biofilm derived devices and systems.